The Modern Online Democracy: An Evaluation of Social Media’s Ability to Facilitate Political Discourse - Choi, Hojun (Technium Social Sciences Journal, 2020)
In an ideal democracy, the opinions of individuals form the basis of societal decision-making as they exercise critical thinking and take part in political discourse to form opinions they take to the voting booths. This formation of opinions, however, is increasingly being affected by social media platforms that provide features that affect with who and in what way people interact with each other. This study will evaluate these effects that social media can have on the formation of political opinions by examining the two representative platforms Facebook and Twitter. These platforms will be evaluated for their abilities to allow freedom of expression, expose users to diverse opinions, and promote user engagement in civil political discussion. Overall, the effects are mixed due to a number of factors, and taking these conclusions into account the study also provides policy suggestions for humanity’s future intertwined with social media.